FC Gamma receptor iii polymorphisms as risk factors for systemic lupus erythematosus in black South African patients - Bloch, Nerissa Wendy (My University, 2017)
Introduction: Systemic lupus erythematosus (SLE) is a multi-system autoimmune disease of unknown aetiology. There is growing evidence environmental factor(s) trigger the disease in the genetically susceptible host. Fragment crystallisable receptor (FCR) genes encode receptors that recognise the fragment crystallisable (Fc) portion of immunoglobulins (IgG) play an important role in the removal of antigen-antibody complexes from the circulation. Genes that code for these receptors have shown to be associated with susceptibility to SLE in various populations. The aim of the present study is to determine the role of single nucleotide polymorphisms (SNPs), allotypes and copy number variations of FC Gamma receptor genes IIIA and IIIB in susceptibility for the Black South Africans with SLE. Methods: DNA from 162 Black South African SLE patients and 155 matched controls were investigated using Taqman assays to determine SNP genotyping differences (FCGRIIIA) and copy number variation (CNV) number (FCGRIIIB). A PCR was optimised in order to determine the allotype differences (FCGRIIIB) via agarose gel electrophoresis. Statistical analyses were then performed on the data to see if the results displayed significance in susceptibility to SLE. Results: The minor allele of the allotypes (FCGRIIIB) and the rs396991 SNP (FCGRIIIA) were not statistically significant in conferring susceptibility to SLE in cases or controls. The rs10127393 SNP (FCGRIIIA) was shown to be monomorphic within both cases and controls for the T allele and is not associated with SLE. The cumulative percentage of copy numbers (FCGRIIIB) ≤2 copies were 0.6% larger in cases than seen in controls. Although this was not significant, this was what has been previously suggested in the literature. Almost half of the cases (43.8%) had lupus nephritis (LN). Upon investigation the NA1/NA2 alleles were found to confer susceptibility to LN (p=0.018), whereas the rs396991 G allele did not (p=0.643). Conclusion: In this study the allotypes, SNPs and CNV investigated were not found to confer susceptibility to SLE. However, subtle trends suggest that further studies are required with larger sample sizes to acquire more data. Almost half of the cases were diagnosed with LN and the NA2 allele was shown to be a risk factor in developing LN.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Medicine. Johannesburg, June 2017
Keywords: FC Gamma Receptor III Polymorphisms Lupus